(untitled) (Colombia Medica, 2023)
Objective: To analyze the agreement between body mass index (BMI) and waist-to-height Ratio (WHtR) to identify preschool and school children with cardiovascular risk factors (CRFs). Methods: 321 kids were included in this cross-sectional study, divided into preschool (3 to 5 years) and school children (6 to 10 years). BMI was used to classify children as overweight or obese. Abdominal obesity was defined with a WHtR≥0.50. Fasting blood lipids, glucose and insulin were measured, and the homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. The presence of CRFs and multiple non-waist circumference (non-WC) metabolic syndrome factors (MetS-Factors) [high HOMA-IR, high triglycerides and low high-density lipoprotein cholesterol (HDL-C)] were analyzed. Results: 112 preschool and 209 school children were evaluated. WHtR≥0.50 classified abdominal obesity in more than half of the preschool children, exceeding those classified with overweight+obesity by BMI (59.5% vs. 9.8%; p<0.001). There was no agreement between WHtR and BMI to identify preschool kids with CRFs and multiple non-WC MetS-Factors (kappa: 0.0 to 0.23, p>0.05). There were similar proportions of school children classified with abdominal obesity by the WHtR and overweight+obesity by the BMI (18.7% vs. 24.9%; p>0.05). There was substantial agreement between WHtR and BMI to identify school children with high total cholesterol values, low-density lipoprotein cholesterol (LDL-C), triglycerides, non-HDL-C, insulin, HOMA-IR, low HDL-C values, and the presence of multiple non-WC MetS-Factors (kappa: 0.616 to 0.857, p<0.001). Conclusion: In preschool children WHtR>=0.5 disagree with BMI results, but in school kids, it has good agreement with the BMI to classify the children´s nutritional status and to identify those with CRFs.